Effects of lipid headgroup and packing stress on poly(ethylene glycol)-induced phospholipid vesicle aggregation and fusion. - Yang, Q (1997)
The effect of lipid headgroup and curvature-related acyl packing stress on PEG-induced phospholipid vesicle aggregation and fusion were studied by measuring vesicle and aggregate sizes using the quasi-elastic light scattering and fluorescence energy transfer techniques. The effect of the lipid headgroup was monitored by varying the relative phosphatidylcholine (PC) and phosphatidylethanolamine (PE) contents in the vesicles, and the influence of hydrocarbon chain packing stress was controlled either by the relative amount of PE and PC content in the vesicles, or by the degree of unsaturation of the acyl chains of a series of PEs, e.g., dilinoleoylphosphatidylethanolamine (dilin-PE), lysophosphatidylethanolamine (lyso-PE), and transacylated egg phosphatidylethanolamine (TPE). The PEG threshold for aggregation depends only weakly on the headgroup composition of vesicles. However, in addition to the lipid headgroup, the curvature stress of the monolayer that forms the vesicle walls plays a very important role in fusion. Highly stressed vesicles, i.e., vesicles containing PE with highly unsaturated chains, need less PEG to induce fusion. This finding applies to the fusion of both small unilamellar vesicles and large unilamellar vesicles. The effect of electrostatic charge on vesicle aggregation and fusion were studied by changing the pH of the vesicle suspension media. At pH 9, when PE headgroups are weakly charged, increasing electrostatic repulsion between headgroups on the same bilayer surface reduces curvature stress, whereas increasing electrostatic repulsion between apposing bilayer headgroups hinders intervesicle approach, both of which inhibit aggregation and fusion, as expected.